ANALISIS TINGKAT KEPUASAN PELAKU USAHA MIKRO DAN KECIL TERHADAP PELAYANAN SERTIFIKASI HALAL SELF DECLARE - Hastuti, Dewi; Maharani, Farikha; Subekti, Endah; Takhim, M; Husna, Asmaul (International Journal Mathla’ul Anwar of Halal Issues, 2024)
Abstract. The halal product process assistant (P3H) plays an important role in managing self-declaration halal certification, namely as a person who assists micro and small entrepreneurs (MSEs) to declare the halalness of their digital-based products. Services that are not maximized can reduce the trust and number of MSEs to take care of halal certificates. The originality of this research lies in a comprehensive study of business actor satisfaction with P3H performance. This study aims to identify and measure business actor satisfaction and analyze attributes that are very important in influencing the quality of P3H services. The respondents of this study were 100 MSEs who had obtained halal certificates through P3H assistance. The research method is the Importance Performance Analysis (IPA) method which is then plotted using the Cartesian Diagram and the Customer Satisfaction Index (CSI) method.   The results showed that the IPA calculation had a suitability level value of 97.75% and on the Cartesian Diagram of 19 attributes there were 2 attributes that required improvement and improvement, namely attribute number 3 (tangibles) and 16 (assurance). The results of the calculation of the Customer Satisfaction Index (CSI) method get a score of 88.51%, indicating that MSE businesses feel "very satisfied" because the score is in the scale range of 81% to 100%, so it can be said that P3H's performance is very good. This study implies that P3H must continue to improve service quality, especially attributes whose service value is less than satisfactory and can maintain or improve attributes that are very important and very satisfying in order to increase satisfaction with self-declare halal certification services.